Antitesis Orang Jujur dan Orang Fasik Dalam Pembentukan Karakter Pemimpin: Studi Eksegesis Amsal 11:11 - Pattinaja, Aska Aprilano; Suhun, Wakinus (Vieka Wahana Semesta, 2024)
Abstract: In general elections, all citizens cast their votes to choose leaders for a nation. The reality today is that there are leaders who are authoritarian, corrupt, nepotistic, use state facilities for personal interests, commit injustice, do not pay attention to the welfare of the people, and others, which are caused by the mistakes of the community in electing these leaders. People need to be educated so that they have an idea of how to choose quality leaders who have the right character and personality. Proverbs 11:11 explains the antithesis of